SISTEM PENDIDIKAN KEAGAMAAN ANTI KORUPSI - Atiqullah Atiqullah (Institut Agama Islam Negeri Madura)
AbstractThis article presents three important aspects of an Islamic education system, namely the purpose of education, curriculum, and strong leadership system. Empowerment of the sub system of religious education is always be prophetic moral messages for the life of the community's anti-corruption in the form of instilled-honesty values, exemplary of the leaders of institutions’ values, as well as oriented curriculum, namely Manhaj al-Tarbiyah al-Islamiyah, Wasilat al-Tarbiyah al-Islamiyah, Kayfiyat al-Tarbiyah al-Islamiyah, and Thariqat al-Tarbiyah al-Islamiyah are methodology and strategy in the process of achieving Islamic education, namely self actualized.Kata-kata kunciperilaku korupsi, sistem pendidikan, tujuan, kurikulum, dan kepemimpinan